Administrative Liability for Violations of Fire Safety Requirements at Rental Facilities - A. Yu. Shatokhin (Сибирское юридическое обозрение, 2020)
The article examines the issue of administrative liability of the lessee and the lessor for violations of fire safety requirements in the existing legal regime for leasing buildings (premises). The urgency of the issue under study is substantiated based, first of all, on the existing contradictory judicial practice. The article analyzes the normative legal acts of the Russian Federation that regulate rental legal relations and administrative liability for violation of fire safety requirements, examines specific law enforcement acts, including those of the Constitutional and Supreme Court of the Russian Federation, studies publications of foreign authors on similar issues. The position of a number of judicial authorities on the impossibility of changing the public obligations of the parties to fulfill the fire safety requirements established by the legislation of the Russian Federation by a lease agreement that regulates only their civil obligations is criticized. The study revealed the characteristic features of a lease agreement, such as: direct transfer of things for temporary possession and use, or for temporary use; the temporary nature of the parties' agreement; concessionality of the contract. Considered, proposed by a number of authors, the classification of fire safety requirements into capital (constructive) and regime (operational, functional) and their author's definitions of these terms, based on the results of which their artificiality and incorrectness are justified. The Author has developed a law-based dichotomous classification and corresponding terminology. The possibility of classifying all fire safety requirements into social and technical requirements has been substantiated. It is proposed to consider as social requirements a set of legal norms that establish the rules of human behavior, the procedure for organizing production and (or) maintaining territories, buildings, structures, premises of organizations in order to ensure fire safety. The requirements of a technical nature should include a set of legal norms aimed at protecting people and property from the effects of hazardous fire factors directly related to the structural space-planning features of premises, buildings, technological equipment installed in it, and engineering systems. The following conceptual thesis has been formulated – the lessor is obliged to fulfill at his own expense the fire safety requirements of a technical nature established for the leased property, and the lessee is obliged to maintain the property in good condition, bear the cost of its maintenance and comply with fire safety requirements of a social nature, unless otherwise provided law, other legal acts or lease agreement. The author proposes to reflect the issue of the division of administrative responsibility between the lessee and the lessor at the level of the Supreme Court of the Russian Federation, in the next review of judicial practice.